POLA KOMUNIKASI VIRTUAL PADA PENGGUNA APLIKASI NIMOTV DIKALA PANDEMI - Widyariani, Ida Ayu Cintya; Joni, I Dewa Ayu Sugiarica; Suryawati, I Gusti Agung Alit; Damasemil, Calvin (E-Jurnal Medium, 2023)
This study discusses the Virtual Communication Patterns for Users of the Nimo TV Application During a Pandemic. This study aims to look at the communication patterns that occur between the host and viewer who carry out the virtual communication process without face-to-face during a pandemic through live streaming media. The research conducted is descriptive qualitative using observation and interview methods as the host and viewer in order to obtain data that is in accordance with the research. The results of this study indicate that the communication pattern that occurs between the host and viewer in the Nimo TV live streaming application is a two-way traffic communication pattern with the type of public communication. As for this study, it was found that the success factors and the obstacle factors for the occurrence of virtual communication in the Nimo TV live streaming application. Keywords: Virtual Communication Patterns, Live Streaming, Nimo TV Application